Women in Filipino Religion-Themed Films - Cabanawan, Erika Jean (Review of Women's Studies, 2011)
This study looks at four Filipino films - Mga Mata ni Angelita, Himala, Ang Huling Birhen sa Lupa, Santa Santita - that are focused on the discourse of religiosity and featured a female protagonist who imbibes the image and role of a female deity. Using a feminist framework, it analyzes the subgenre's connection and significance to the Filipino consciousness of a female God, and the imaging of the Filipino woman in the context of a hybrid religion. The study determines how religion is used in Philippine cinema, and whether or not it promotes enlightenment. The films' heavy reference to religious and biblical images is also examined as strategies for myth-building.